Resource partitioning among bat species in Peninsular Malaysia rice fields - Nur-Izzati Abdullah; Nurul-Ain Elias; Nobuhito Ohte; Christian Vincenot (PeerJ, 2024)
Resource partitioning among tropical bats in agricultural areas of Peninsular Malaysia remains unclear. This study was conducted to evaluate resource partitioning among bats by examining their fecal samples. The main bat species sampled included: Rhinolophus coelophyllus, Rhinolophus malayanus, Rhinolophus pusillus, Rhinolophus refulgens, Taphozous melanopogon and Hipposideros larvatus. Two harp traps were set at different elevations on a hilltop (Gunung Keriang) and two high nets were used in neighboring rice fields at three sites, for three consecutive nights per sampling from April 2021 to February 2022. A total of 301 bats and 1,505 pellets were analyzed using a conventional approach which examined the fecal sample under the microscope. All of the bat species within the study had insects from the order Coleoptera, Lepidoptera, Diptera and Hemiptera in their diet. Larger bats exhibited a greater variety of prey consumption. Male individuals were observed to be generalists while female individuals were specialists, particularly during pregnancy and lactating reproductive stages. Bat species and insect order had a significant impact on the percentage fragment frequency of the insects consumed. Rhinolophus coelophyllus specialized in feeding on Coleoptera and Diptera, H. larvatus fed on Coleoptera, R. malayanus fed on Hemiptera, R. pusillus and T. melanopogon fed on Lepidoptera. Future molecular analysis can be carried out to further identify the insect pests consumed by these bats up to species level. These findings enhance our understanding of bats’ ecological roles in agricultural landscapes and contribute to conservation and pest management strategies.